1973
DOI: 10.1104/pp.51.6.1082
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced Ethylene Production in Sorghum

Abstract: Ethylene production was induced in sections of dark-grown Sorghum vulgare L. seedlings by treatment with light in the blue and far red regions of the light spectrum. The action spectrum closely resembled the previously reported spectra for high irradiance response; thus, light-induced ethylene production is probably a high irradiance response with phytochrome as the initial photoreceptor.Ethylene production in plant tissue may be regulated by light. Two modes of regulation are frequently encountered.In one, et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

1975
1975
1993
1993

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 9 publications
2
9
1
Order By: Relevance
“…Response to endogenous ethylene may, of course, be even more rapid than to the applied gas. The action spectrum for ethylene biosynthesis determined by Craker et al (4) resembles the action spectrum for phototropism in that both are induced primarily by blue light. Ethylene biosynthesis also exhibits a narrow peak in the far red, which phototropism does not.…”
Section: Resultsmentioning
confidence: 94%
“…Response to endogenous ethylene may, of course, be even more rapid than to the applied gas. The action spectrum for ethylene biosynthesis determined by Craker et al (4) resembles the action spectrum for phototropism in that both are induced primarily by blue light. Ethylene biosynthesis also exhibits a narrow peak in the far red, which phototropism does not.…”
Section: Resultsmentioning
confidence: 94%
“…A high irradiance blue or far red enhancement of ethylene production has also been found (CRAKER et al 1973), indicating that the effect of illumination on ethylene production depends strongly on both wavelength and intensity. GEPSTEIN and THIMANN (1980) found that high-intensity white light reduces ethylene production in leaves and suggested that the consequent rise in ethylene production in the dark accounts for certain photoperiodic effects such as nyctinasty.…”
Section: Effects On Ethylenementioning
confidence: 93%
“…Ethylene evolution was found to be controlled by phytochrome. The reduction of ethylene level by red irradiation was correlated with bean hook opening (12, 13), pea plumular grovrth (6,7), carotenoid synthesis in peas (9), anthocyanin synthesis in cabbage (11) and enhancement of geotropic sensitivity (10), An increase in ethylene evolution in etiolated sorghum seedlings by blue and FR light was reported by Cracker et al (2).…”
Section: Introductionmentioning
confidence: 83%